Between Rhetoric and Reality: Learnings From Youth Participation in the Adolescent and Youth Health Policy in South Africa - Tanya Jacobs; Asha George (Kerman University of Medical Sciences, 2022)
Background  Youth participation makes an essential contribution to the design of policies and with the appropriate structures, and processes, meaningful engagement leads to healthier, more just, and equal societies. There is a substantial gap between rhetoric and reality in terms of youth participation and there is scant research about this gap, both globally and in South Africa. In this paper we examine youth participation in the Adolescent and Youth Health Policy (AYHP) formulation process to further understand how youth can be included in health policy-making.Methods  A conceptual framework adapted from the literature encompassing Place, Purpose, People, Process and Partnerships guided the case study analysis of the AYHP. Qualitative data was collected via 30 in-depth, semi-structured interviews with policy actors from 2019-2021.Results  Youth participation in the AYHP was a 'first' and unique component for health policy in South Africa. It took place in a fragmented policy landscape with multiple actors, where past and present social and structural determinants, as well as contemporary bureaucratic and donor politics, still shape both the health and participation of young people. Youth participation was enabled by leadership from certain government actors and involvement of key academics with a foundation in long standing youth research participatory programmes. However, challenges related to when, how and which youth were involved remained. Youth participation was not consistent throughout the health policy formulation process. This is related to broader contextual challenges including the lack of a representative and active youth citizenry, siloed health programmes and policy processes, segmented donor priorities, and the lack of institutional capability for multi-sectoral engagement required for youth health.Conclusion  Youth participation in the AYHP was a step toward including youth in the development of health policy but more needs to be done to bridge the gap between rhetoric and reality.